CLINICAL ASSESSMENT AND TREATMENT OF OCCLUSAL CHANGES IN CHILDREN'S DENTAL ARCHES (Web of Teachers: Inderscience Research, 2025)
This article examines occlusal changes in children's dental arches, their clinical diagnosis, and treatment methods. The primary causes of occlusal disorders, modern approaches to their correction, and preventive measures are discussed. The study highlights the importance of early intervention in managing occlusal irregularities to prevent more severe dental and maxillofacial anomalies in the future.